2010
DOI: 10.1016/j.conb.2010.08.021
|View full text |Cite
|
Sign up to set email alerts
|

The behavioral neuroscience of anuran social signal processing

Abstract: Acoustic communication is the major component of social behavior in anuran amphibians (frogs and toads) and has served as a neuroethological model for the nervous system's processing of social signals related to mate choice decisions. The male's advertisement or mating call is its most conspicuous social signal, and the nervous system's analysis of the call is a progressive process. As processing proceeds through neural systems, response properties become more specific to the signal and, in addition, neural ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
43
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(44 citation statements)
references
References 59 publications
1
43
0
Order By: Relevance
“…female phonotaxis and male antiphonal calling behavior (Diekamp and Gerhardt, 1995;Gerhardt, 1974;Gerhardt, 1981a;Gerhardt, 1981b;Gerhardt, 1991;Simmons et al, 1993) mate attraction signals -and synthetic stimuli with similar spectral-temporal features are processed selectively or with enhanced responsiveness by neurons in many brain regions [as revealed in electrophysiology studies (Diekamp and Gerhardt, 1995;Eggermont and Epping, 1986;Elliott et al, 2011;Fuzessery and Feng, 1983;Miranda and Wilczynski, 2009a;Miranda and Wilczynski, 2009b;Rose et al, 1985) and immediate early gene studies (Chakraborty et al, 2010;Hoke et al, 2004;Hoke et al, 2008;Lynch and Wilczynski, 2008;Mangiamele and Burmeister, 2011)]. In anuran amphibians, this is particularly apparent in the midbrain (reviewed in Rose and Gooler, 2007;Wilczynski and Ryan, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…female phonotaxis and male antiphonal calling behavior (Diekamp and Gerhardt, 1995;Gerhardt, 1974;Gerhardt, 1981a;Gerhardt, 1981b;Gerhardt, 1991;Simmons et al, 1993) mate attraction signals -and synthetic stimuli with similar spectral-temporal features are processed selectively or with enhanced responsiveness by neurons in many brain regions [as revealed in electrophysiology studies (Diekamp and Gerhardt, 1995;Eggermont and Epping, 1986;Elliott et al, 2011;Fuzessery and Feng, 1983;Miranda and Wilczynski, 2009a;Miranda and Wilczynski, 2009b;Rose et al, 1985) and immediate early gene studies (Chakraborty et al, 2010;Hoke et al, 2004;Hoke et al, 2008;Lynch and Wilczynski, 2008;Mangiamele and Burmeister, 2011)]. In anuran amphibians, this is particularly apparent in the midbrain (reviewed in Rose and Gooler, 2007;Wilczynski and Ryan, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…In H. cinerea and other anurans, the importance of communication signals is reflected in specializations in the neural systems processing them. Communication signals -particularly mate-attraction signals -and synthetic stimuli with similar spectral-temporal features are processed selectively or with enhanced sensitivity throughout the auditory system, and particularly in the midbrain (Feng et al, 1990;Leary et al, 2008;Rose and Gooler, 2007;Wilczynski and Ryan, 2010). There is good evidence to suggest that exposure to conspecific chorus sounds can influence the hormonal state of the green treefrog and other frogs (Burmeister and Wilczynski, 2000;Burmeister and Wilczynski, 2001;Lynch and Wilczynski, 2006;Wilczynski and Lynch, 2011); however, it is not clear how this exposure to conspecific choruses might alter the neural processing of male calls in the auditory system.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The bulk of auditory afferents terminates in the principal nucleus with projections that mainly terminate at the mesencephalic level. In contrast, magnocellular neurons and especially laminar nucleus neurons do not only project to other auditory centers, but also to premotor and motor centers in the brainstem and medulla oblongata, thus forming an audiomotor interface (Walkowiak and Luksch 1994;Luksch and Walkowiak 1998;Wilczynski and Ryan 2010). Single-unit (Hermes et al 1982), as well as multiunit studies (Mohneke 1983;Schneichel and Schneider 1988) revealed a topic representation of tones in the torus.…”
Section: Torus Semicircularismentioning
confidence: 99%
“…However, several investigators have assumed that each species-specific property is relevant to the conspecific animal (see review by Wilczynski and Ryan 2010). Therefore, the sound stimuli used in this study have been chosen to be simple and complex tone bursts, which have carrier frequencies similar to those extracted from the mating call of the toad Bufo regularis.…”
Section: Discussionmentioning
confidence: 99%